A LITERATURE REVIEW ON GREEN SUPPLY CHAIN MANAGEMENT ADOPTION DRIVERS - Masudin, Ilyas (Jurnal Ilmiah Teknik Industri, 2019)
This article provides a systematic literature review of the driving factors influencing the application of green supply chain management (GSCM). The GSCM adoption issues have been widely given attention by researchers and practitioners since the adoption of GSCM would impact significantly on an organization's environmental, social, and financial performance. Most GSCM adoption has been discussed in the perspective of logistics management activities such as procurement, manufacturing, transportation, and reverse logistics. Nowadays, the discussion of GSCM adoption in terms of the driving factors affecting a successful GSCM application has led to complexity. In this article, a further review and discussion are conducted in terms of the driving factors dealing with GSCM adoption, including three major points, such as the driving forces of green procurement, green manufacturing, and green distribution and reverse logistics adoption. The driving factors are reviewed to highlight the recent factors affecting GSCM adoption.  In this article, 94 papers from the past study are presented, associating each point of the discussion.